2017
DOI: 10.1038/s41598-017-04375-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic, proteomic and phosphoproteomic analysis of C. elegans embryos with a focus on ham-1/STOX and pig-1/MELK in dopaminergic neuron development

Abstract: Asymmetric cell divisions are required for cellular diversity and defects can lead to altered daughter cell fates and numbers. In a genetic screen for C. elegans mutants with defects in dopaminergic head neuron specification or differentiation, we isolated a new allele of the transcription factor HAM-1 [HSN (Hermaphrodite-Specific Neurons) Abnormal Migration]. Loss of both HAM-1 and its target, the kinase PIG-1 [PAR-1(I)-like Gene], leads to abnormal dopaminergic head neuron numbers. We identified discrete gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The pig-1 single and pig-1 ham-1 double mutants, however, produce similar Q.a DCSA phenotypes ( Fig S2). The same epistatic interactions between ham-1 and pig-1 were previously observed for other lineages [8,18].…”
Section: Pig-1 Does Not Mediate the Regulation Of Qa Dcsa By Ham-1supporting
confidence: 82%
“…The pig-1 single and pig-1 ham-1 double mutants, however, produce similar Q.a DCSA phenotypes ( Fig S2). The same epistatic interactions between ham-1 and pig-1 were previously observed for other lineages [8,18].…”
Section: Pig-1 Does Not Mediate the Regulation Of Qa Dcsa By Ham-1supporting
confidence: 82%
“…elegans nonmuscle myosin II NMY-2 has been proposed to be a target of PIG-1 MELK [ 19 , 40 ]. Furthermore, NMY-2 phosphorylation at two specific residues, serine 211 (S211) and serine 1974 (S1974), was found to be reduced in pig-1 mutants [ 41 ]. Using a nmy-2 CRISPR knock-in allele that produces a functional NMY-2::GFP fusion protein ( nmy-2 ( cp13 ), nmy-2 :: gfp + LoxP ) [ 42 ], we visualized NMY-2 in the NSMnb.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of these studies revealed that most extra cells arise appear to arise from 21 of 34 (32 embryonic and 2 post-embryonic) neuroblast divisions that produce an anterior cell fated to die and a posterior cell that survives and adopts either a neuronal or mitotic fate [ 1 , 2 ] ( Table 1 )( Fig 1 ). The ham-1 mutant HSN/PHB, ALN/PLM and CEPD/URX lineages are also missing neurons, resulting from either ectopic apoptosis or a failure of the neurons to differentiate and to express the appropriate marker [ 7 , 14 , 15 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%